Neddylation, an Emerging Mechanism Regulating Cardiac Development and Function - Li, Jie; Zou, Jianqiu; Littlejohn, Rodney; Liu, Jinbao; Su, Huabo (Frontiers in Physiology, 2020)
Defects in protein quality control have been increasingly recognized as pathogenic factors in the development of heart failure, a persistent devastating disease lacking efficacious therapies. Ubiquitin and ubiquitin-like proteins, a family of post-translational modifying polypeptides, play important roles in controlling protein quality by maintaining the stability and functional diversity of the proteome. NEDD8 (neural precursor cell expressed, developmentally downregulated 8), a small ubiquitin-like protein, was discovered two decades ago but until recently the biological significance of NEDD8 modifications (neddylation) in the heart has not been appreciated. In this review, we summarize the current knowledge of the biology of neddylation, highlighting several mechanisms by which neddylation regulates the function of its downstream targets, and discuss the expanding roles for neddylation in cardiac physiology and disease, with an emphasis on cardiac protein quality control. Finally, we outline challenges linked to the study of neddylation in health and disease.